Association Between the Development of Subclinical Cardiovascular Disease and Human Immunodeficiency Virus (HIV) Reservoir Markers in People With HIV on Suppressive Antiretroviral Therapy. (8th November 2022) - Turcotte, Isabelle; El-Far, Mohamed; Sadouni, Manel; Chartrand-Lefebvre, Carl; Filali-Mouhim, Ali; Fromentin, Rémi; Chamberland, Annie; Jenabian, Mohammad-Ali; Baril, Jean-Guy; Trottier, Benoit; Thomas, Réjean; Tremblay, Cécile L; et al.
Abstract: We report that people with human immunodeficiency virus (HIV) diagnosed with coronary artery atherosclerotic plaques display higher levels of HIV DNA compared with those without atherosclerotic plaques. In a multivariable prediction model that included 27 traditional and HIV-related risk factors, measures of HIV DNA were among the most important predictors of atherosclerotic plaque formation.